2018
DOI: 10.1007/s12630-018-1082-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-pressurized air-Q® intubating laryngeal airway versus the LMA® Classic™: a randomized clinical trial

Abstract: www.clinicaltrials.gov (NCT02206438). Registered 1 August 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Higher scores may be associated with better sealing and ventilation. [ 20 ] The fiber-optic view of the larynx through Air-Q SP was better than that of Proseal LMA as previously reported. [ 5 8 10 ] This may be due to the structural difference in the Air-Q SP airway tube; it is larger and more preformed than the Proseal LMA, which has a drain tube which is next to the ventilation channel and passes through the much deeper cuff container to terminate distally in the mid-line.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Higher scores may be associated with better sealing and ventilation. [ 20 ] The fiber-optic view of the larynx through Air-Q SP was better than that of Proseal LMA as previously reported. [ 5 8 10 ] This may be due to the structural difference in the Air-Q SP airway tube; it is larger and more preformed than the Proseal LMA, which has a drain tube which is next to the ventilation channel and passes through the much deeper cuff container to terminate distally in the mid-line.…”
Section: Discussionmentioning
confidence: 51%
“…Clinical studies have compared Air-Q SP and other SADs for OLP showing variable results. [ 1 2 5 19 20 21 ] The initial study was carried out to assess the feasibility of Air-Q-SP in clinical practice and generate data for future comparison trials in 352 children using sizes of 1.0, 1.5, 2.0, and 2.5. [ 1 ] The mean OLP was 17.8 ± 5.4 and 20.4 ± 5.5 cmH 2 O at baseline and 10 min, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PLMA is constructed from silicone, which conforms adequately to supraglottic structures better than PVC, with intra-cuff pressure maintained at 60 cmH 2 O, a significantly higher OLP was found in the SP Blocker group due to the better seal provided by the non-inflatable cuff of the SP Blocker beside its unique design features: the anterior curve of its airway tube that approximates the oropharyngeal airway providing stable end-to-end coupling with the glottis, mask ridges that stabilize the bowl transversely and higher posterior heel height that improves the seal at the tongue [ 38 , 39 ]. Our results clinically corroborate two studies showing that the mean OLP of the Air-Q Blocker and Air-Q SP became higher than that of the PLMA, but they did not agree with a study which found that Air-Q ILA has a lower mean OLP than the PLMA, while previous studies found no statistically significant differences when comparing either the Air-Q ILA and the PLMA or the Air-Q Blocker and the PLMA [ 6 , 31 , 40 – 42 ].…”
Section: Discussionmentioning
confidence: 99%